The level of political knowledge in Slovenia - Novak, Meta (Journal of comparative politics, 2014)
Delli Carpini and Keeter showed that political knowledge is more or less general, meaning that informed citizens are usually informed in all aspects of political knowledge. Unfortunately, political knowledge is not evenly distributed. This is even more problematic when we keep in mind that the politically informed are also more politically active. The aim of this paper is to find out how informed Slovenians are as citizens of a young post-socialist democracy and who is informed. We used data from the European Election Study 2009 and performed a simple comparison of mean values and a linear regression model. Slovenians turned out to be moderately knowledgeable, with higher levels of EU political knowledge in comparison to national political knowledge. Slovenians were also among the most knowledgeable citizens in the EU member states. Differences in the level of knowledge are present between males and females, education groups and classes, based on the level of news attention and political interest.
Keywords: Citizens; Državljani; Political participation; Politična participacija